Investigações da vegetoterapia caracteroanalítica pós-reichiana sobre sintomas depressivos - Jaques Neto, Eduardo Francisco (My University, 2025)
Recent data indicate that around 280 million people worldwide suffer from some form of depressive spectrum disorder, with depression being the leading cause of disability among mental health disorders. Given the severity and complexity of this scenario, this study is based on the following research question: What are the possible articulations between the clinical understandings of post-Reichian character-analytic vegetotherapy and the etiologies of depressive symptoms? From this problem, the general objective was established: to identify possible articulations between the aforementioned approach and the origins of depressive symptoms. The specific objectives were: (1) to distinguish the basic character structures and covering characterial traits presented by individuals with depressive symptoms; (2) to understand the presence or absence of somatopsychopathologies; and (3) to describe the somatopsychodynamics present in these individuals. This is a qualitative study with four participants residing in the municipality of Torres (RS) and neighboring cities, selected through the application of the Beck Depression Inventory (BDI-II) and later invited for interviews. Data collection consisted of one meeting for the application of the instrument and three individual meetings, according to inclusion criteria. The information obtained was analyzed using content analysis, from which categories emerged that responded to the proposed objectives. The characterial traits detected among the participants were hysterical, masochistic, compulsive, and oral. Regarding orality, the reports on breastfeeding and weaning indicated significant frustrations in the oral phase, according to the post-Reichian perspective. Thus, participants A and D were classified as repressed oral subtype, and participants B and C as dissatisfied oral subtype. The body assessments conducted according to character-analytic vegetotherapy revealed armoring especially in the first two segments, with emphasis on the oral segment. The somatopsychopathologies observed were anxiety, anguish, and dysthymia. Considering the set of information - participants' responses, characterological analyses, and body assessments - it was concluded that all participants present a borderline basic character structure, classically associated with depressive disorders in post-Reichian theory. [resumo fornecido pelo autor]
Dados recentes indicam que cerca de 280 milhões de pessoas no mundo sofrem com algum transtorno do espectro depressivo, sendo a depressão a principal causa de incapacidade dentre as desordens de saúde mental. Dada a gravidade e complexidade desse cenário, este estudo parte da seguinte questão de pesquisa: Quais as possíveis articulações entre as compreensões clínicas da vegetoterapia caracteroanalítica pós-reichiana e etiologias dos sintomas depressivos? A partir dessa problemática, estabeleceu-se como objetivo geral identificar possíveis articulações entre a referida abordagem e origens de sintomas depressivos. Os objetivos específicos consistiram em: (1) distinguir as estruturas caracterológicas de base e as caracterialidades de cobertura apresentadas por sujeitos com sintomas depressivos; (2) compreender a presença ou ausência de somatopsicopatologias; e (3) descrever a somatopsicodinâmica presente nesses sujeitos. Trata-se de um estudo qualitativo, com quatro participantes residentes no município de Torres (RS) e cidades vizinhas, selecionados mediante aplicação do Inventário de Depressão de Beck (BDI-II) e posterior convite para realização de entrevistas. A coleta de dados foi composta por um encontro para aplicação do instrumento e três encontros individuais, conforme os critérios de inclusão. As informações obtidas foram analisadas por meio da técnica de análise de conteúdo, da qual emergiram categorias que responderam aos objetivos propostos. As caracterialidades detectadas entre os participantes foram os traços histérico, masoquista, compulsivo e oral. Com relação à oralidade, os relatos sobre amamentação e desmame apontaram frustrações importantes na fase oral, de acordo com a perspectiva pós-reichiana. Assim, classificou-se as participantes A e D como subtipo oral reprimido, e os participantes B e C como subtipo oral insatisfeito. As avaliações corporais realizadas segundo a vegetoterapia caracteroanalítica revelaram encouraçamento especialmente nos dois primeiros segmentos, com destaque para o segmento oral. As somatopsicopatologias observadas foram ansiedade, angústia e distimia. Considerando o conjunto das informações - respostas dos sujeitos, análises caracterológicas e avaliações corporais -, concluiu-se que todos os participantes apresentam estrutura caracterológica de base borderline, classicamente associada aos transtornos depressivos na teoria pós-reichiana. [resumo fornecido pelo autor]
Keywords: Depressão; Psicologia; Saúde mental; Depression; Psychology; Mental health